The Identification of Seasonality in the Housing Market Using the X13-ARIMA-SEATS Model - Łukasz Mach; Ireneusz Dąbrowski; Daria Wotzka; Paweł Frącz (Ekonometria)
Aim: In the conducted research, profiles of seasonality in the housing market were determined, which provided an opportunity to answer two fundamental questions: what is the nature of harmonic variation in the seasonality and periodicity of the studied components of the construction process? what parameters of the ARIMA model optimally describe the construction market?